1995
DOI: 10.1002/app.1995.070570902
|View full text |Cite
|
Sign up to set email alerts
|

New perfluoropolyether soft segment containing polyurethanes

Abstract: New segmented polyurethanes (FPU) with perfluoropolyether (PFPE) blocks have been synthesized by a two‐step process. In the first step, a fluorinated isocyanate end‐capped prepolymer has been obtained by reaction of a fluorinated macrodiol with alicyclic diisocyanates in the presence of solvent. The following chain extension has been carried out by reaction of the prepolymer with short hydrogenated polyols giving a polymeric matrix. Tensile properties, dynamical–mechanical (DMA), and calorimetric (DSC) analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…1 Di-and monohydroxy-terminated perfluoropolyethers (Fomblin  PFPE, Ausimont) can be used as speciality lubricants 2 for magnetic recording media as well as building blocks 3 for the preparation of macromersegmented copolymers: In particular, copolymerization of PFPE macroalcohols with di-or polyisocyanates such as R-(N C O) x , with x D 2 or 3, leads to polyurethane materials as elastomers 4,5 and coatings. 6,7 A specific study was reported in the recent literature 8 on the spectroscopic and tensiometric characterization of cross-linked solvent-borne PFPE-containing coatings, showing an efficient surface enrichment in fluorine, even in polyphasic three-dimensional networks.…”
Section: Introductionmentioning
confidence: 99%
“…1 Di-and monohydroxy-terminated perfluoropolyethers (Fomblin  PFPE, Ausimont) can be used as speciality lubricants 2 for magnetic recording media as well as building blocks 3 for the preparation of macromersegmented copolymers: In particular, copolymerization of PFPE macroalcohols with di-or polyisocyanates such as R-(N C O) x , with x D 2 or 3, leads to polyurethane materials as elastomers 4,5 and coatings. 6,7 A specific study was reported in the recent literature 8 on the spectroscopic and tensiometric characterization of cross-linked solvent-borne PFPE-containing coatings, showing an efficient surface enrichment in fluorine, even in polyphasic three-dimensional networks.…”
Section: Introductionmentioning
confidence: 99%
“…10 ZDOL has a good reactivity, [11][12][13][14] and it has been used recently to synthesize polyurethanes. [15][16][17] Moreover, several comprehensive physicochemical studies are available on ZDOL and on some derivatives obtained by end capping the PFPE chain with different hydrogenated end groups; 18 -21 their polarity plays an important role in determining some physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In another variation these diols are capped with isocyanates or blocked isocyanates and these polyisocyanates are then either moisture cured, or used in formulations with other diols to make fluorinated coatings. [15] …”
Section: Fluoropolymer-based Coatingsmentioning
confidence: 97%